2019
DOI: 10.3390/su11092714
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Absorption Performance of Cylindrical and Rectangular Permeable Membrane Space Sound Absorbers Using the Three-Dimensional Boundary Element Method

Abstract: Three-dimensional, permeable membrane space sound absorbers have been proposed as practical and economical alternatives to three-dimensional, microperforated panel space sound absorbers. Previously, the sound absorption characteristics of a three-dimensional, permeable membrane space sound absorber were predicted using the two-dimensional boundary element method, but the prediction accuracy was impractical. Herein, a more accurate prediction method is proposed using the three-dimensional boundary element metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…10 This shape is applicable to 3-D PMA, and is particularly easy to apply to cylindrical 3-D PMA, to offer better designability and luminescence distribution for the aesthetic benefit of sound absorbing technique. 5,6…”
Section: Pseudo-cylindrical Concave Curves (Pccc) Shell Shapementioning
confidence: 99%
See 2 more Smart Citations
“…10 This shape is applicable to 3-D PMA, and is particularly easy to apply to cylindrical 3-D PMA, to offer better designability and luminescence distribution for the aesthetic benefit of sound absorbing technique. 5,6…”
Section: Pseudo-cylindrical Concave Curves (Pccc) Shell Shapementioning
confidence: 99%
“…4 Therefore, in order to determine the expected absorptivity value of the test specimen, we made a BEM simulation for a cylindrical 3-D PMA (without folding) to give a first approximation of expected absorptivity of the test specimens made of the selected material. 6 The method of the BEM simulation was detailed in Toyoda et al 6 As is shown in Fig. 5 of subsequent section, the result of the simulation, with the parameters of the selected material above, showed that the selected material can offer moderately high sound absorptivity, i.e., around 0.5 to 0.6 at middle and high frequencies.…”
Section: Preliminary Check Of Selected Materials By Bem Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…All these numbers show that sound absorbing materials based on fiberglass and mineral wool report high environmental impacts, mainly due to their embodied energies [3]. Moreover, Toyoda et al [4] have pointed out some of the environmental drawbacks of using fiberglass as a sound-absorbing material, including durability issues, difficult recycling, and that its dust is harmful to humans. The acoustic characterization of green materials has been discussed by Iannace [5] and a comprehensive review on acoustical eco-materials can be found in [2].…”
Section: Introductionmentioning
confidence: 99%
“…The statistical sound absorption coefficients of permeable membranes of different airflow resistance and sizes have been presented more recently [12]. On the other hand, Toyoda et al [4] have presented a numerical method to predict the sound absorption performance of cylindrical and rectangular permeable membrane space sound absorbers. Kalinova [9] has demonstrated that the nanofibrous layer has a resonant effect on sound absorption when the nanofibers are arranged with respect to the layer.…”
Section: Introductionmentioning
confidence: 99%